Effects of Medication Adherence in Epilepsy Patients On Quality of Life - Bora GÜLAY; Mustafa Tansel KENDİRLİ; Serkan DEMİR; Ali Rıza SONKAYA; Mehmet Fatih ÖZDAĞ (Archives of Epilepsy, 2018)

(untitled)
Objectives:This study aimed to observe epileptic patients on drug compliance and its effects on their quality of life to reveal the effects of socio-demographic and disease-related characteristics on drug compliance and quality of life.Methods:This study was performed with self-filling and face-to-face interview method with 84 epileptic patients, who were selected by a random sampling method from those who applied to GATA Haydarpaşa Training Hospital, Neurology Polyclinic, between January and June 2014. When data related to patients were collected, an introductive patient interview form, which contains information about the disease, the Morisky Medication Adherence Scale, indicating drug compliance, and the short form-36 scale, which measures quality of life, were used.Results:Patients with a high drug compliance were found to have significantly higher scores on emotional role (p<0.043), viability (p<0.000), mental health (p<0.002), and general health (p<0.000).Conclusion:We recommend making efforts to eliminate the negativity, if there is any, and to increase the quality of life by evaluating the factors that may influence drug compliance in patients on an individual basis considering low drug compliance therefore low quality of life groups.